Fishing boats at dock at Harbor Wharf number 2, Fisherman's Wharf - Albert Walton DeRome:::Creator::::::::::::
Lampara at dock at Harbor Wharf number 2, Fisherman's Wharf, near Booth's Cannery in Monterey, California. The photographer, Albert Walton DeRome (Al Aagard), was a cousin of Carol Henning Steinbeck. (see Steinbeck Studies 15.1 (2004): 18.) See also photo numbers 1-957 & 1-960. Note that this is a photo of the original. The original likely had damage at left and right of photo.